1992
DOI: 10.1139/z92-180
|View full text |Cite
|
Sign up to set email alerts
|

Echolocation behaviour of vespertilionid bats (Lasiurus cinereus and Lasiurus borealis) attacking airborne targets including arctiid moths

Abstract: We observed the echolocation and hunting behaviour of Lasiurus borealis and Lasiurus cinereus from May to August of 1989, 1990, and 1991 to assess the role of feeding buzzes in the behaviour of echolocating bats attacking airborne prey. Feeding buzzes consist of short echolocation pulses produced at a rapid rate just before contact between a flying bat and its prey. The hypothesis that the duration of the feeding buzz reflects the size of the attacked prey was not supported by the data. The mean lengths of sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 22 publications
4
84
1
Order By: Relevance
“…Hipposideros commersoni (Vaughan, 1977), Rhinolophus rouxi (Neuweiler et al, 1987), R. ferrumequinum and R. hipposideros (Jones and Rayner, 1989)]. This in contrast to LDC species, some of which attack inanimate objects in the wild (Acharya and Fenton, 1992;Barclay and Brigham, 1994).…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…Hipposideros commersoni (Vaughan, 1977), Rhinolophus rouxi (Neuweiler et al, 1987), R. ferrumequinum and R. hipposideros (Jones and Rayner, 1989)]. This in contrast to LDC species, some of which attack inanimate objects in the wild (Acharya and Fenton, 1992;Barclay and Brigham, 1994).…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
“…There are many records of bats attacking airborne, insect-sized targets, from small pebbles to dry flies used in fishing (Acharya and Fenton, 1992;Barclay and Brigham, 1994). This raises the question: do HDC echolocators sometimes behave as if they were LDC echolocators?…”
Section: Advantages Of Hdc Echolocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these changes suggest increased time and effort spent searching for and attempting to capture each prey item, and increased occurrence of pauses. Post-capture pauses during echolocation may be used for prey-handling in some bat species (Acharya and Fenton, 1992;. If the same is true for sperm whales, the increased number of transitions into pause state during airgun exposure may indicate increased time spent manipulating and handling prey or possibly increased prey capture success rate.…”
Section: Discussionmentioning
confidence: 99%
“…After a buzz, bats generally pause echolocation click production for a period of several hundred milliseconds to several seconds (Griffin et al, 1960;Kalko and Schnitzler, 1989;Hartley, 1992b;Kalko, 1995;Moss and Surlykke, 2001;Hiryu et al, 2007). The mean duration of the post-buzz pause is often longer after successful captures than after unsuccessful ones (Acharya and Fenton, 1992;. This increase in pause duration may be related to time required for prey handling; however, found that pause duration did not increase as prey size (and thus inferred handling time required) increased.…”
Section: Introductionmentioning
confidence: 99%